Local Ecological Knowledge on Forest Clearing: A Case Study of Parak and Rimbo Practices in Simancuang Community, Indonesia - Asmin, Ferdinal; Darusman, Dudung; Ichwandi, Iin; Suharjito, Didik (Universitas Negeri Semarang, 2016)
Local communities are frequently judged as the main driver of forest degradation and deforestation because of the weak recognition to local ecological knowledge (LEK) or traditional ecological knowledge (TEK). We assessed that it is important to elaborate the attributes of LEK and TEK as a way to describe why and how the local community clears the forest, as well as its relation to local practices, named parak and rimbo. Our research uses case study method to describe the local practices in Simancuang community, Alam Pauh Duo Village, South Solok District, West Sumatra Province. We conducted unstructured interviews, observations, and documents selection which were analyzed through categorization and codification as well as complemented with history analysis, spatial analysis, and related document analysis. The results showed that Simancuang community knowledge can describe the attributes of LEK and TEK as a unified whole of local knowledge for sustaining their livelihoods. Therefore, the forest clearing by Simancuang people is one of the livelihoods strategies, but they were not the main driver of forest degradation and deforestation in South Solok District.